Basic principles and rationale for the use of cognitive training in the system of psychological correction of the maladaptive states of internship doctors - Vyun, V. V. (Journal of Education, Health and Sport, 2016)
The objective: to create a technology for conducting a cognitive training of resistance to stress in internship doctors during adaptation period to their professional activity. 213 persons - internship doctors of theKharkivNationalMedicalUniversity( 116 women and 97 men) underwent complex clinical, anamnestic and psychodiagnostic examination. 20.2% of the examined internship doctors (20.1% of men and 19.1% of women) have signs of lowering the level of work capacity and psychological comfort; In 65.7% of internship doctors (55.7% of men and 68.6% of women) it was revealed the development of maladaptation, showing psychological discomfort in their everyday lives, constant feeling of dissatisfaction with themselves and their professional activities. We have developed and tested a system of psychological correction of maladaptation states of internship doctors, which includes programs for the following psychological and psychosocial trainings; training of prevention of the development of stress reaction, aimed at revealing the pathogenetic nature of the conflict that determines the launch of a neurotic reaction; activation of positive personality traits; correction of emotional reactions; processing of the stereotype of behavior, normalization of the system of emotional-volitional reaction; changing the system of relations. there is a steady positive dynamics of the psychological state, the maladaptive states are reduced; in 92,6% of the examined people, who were being examined for 3 years, recurrences of the violations of adaptation did not occur.